2009
DOI: 10.1007/s11083-009-9117-9
|View full text |Cite
|
Sign up to set email alerts
|

On the Complexity of Cover-Incomparability Graphs of Posets

Abstract: In this paper we show that the recognition problem for C-I graphs of posets is NP-complete. On the other hand, we prove that induced subgraphs of C-I graphs are exactly complements of comparability graphs, and hence the recognition problem for induced subgraphs of C-I graphs of posets is polynomial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The studies on C-I graphs is interesting due to the fact that C-I graphs belong to some interesting classes of graphs like hole-free graphs [8] and perfect graphs [1], but a nice graph-theoretic characterization of C-I graphs is still unknown. It is proved that the recognition complexity of C-I graphs is NP-complete (Maxová et al in [11]). Several authors considered the problem of characterizing C-I graphs from well-known graph families: split graphs, block graphs [6], cographs [7], Ptolemaic graphs [12], distance-hereditary graphs [12], and k-trees [10].…”
Section: Introductionmentioning
confidence: 99%
“…The studies on C-I graphs is interesting due to the fact that C-I graphs belong to some interesting classes of graphs like hole-free graphs [8] and perfect graphs [1], but a nice graph-theoretic characterization of C-I graphs is still unknown. It is proved that the recognition complexity of C-I graphs is NP-complete (Maxová et al in [11]). Several authors considered the problem of characterizing C-I graphs from well-known graph families: split graphs, block graphs [6], cographs [7], Ptolemaic graphs [12], distance-hereditary graphs [12], and k-trees [10].…”
Section: Introductionmentioning
confidence: 99%
“…One possibility is to try to characterize graphs that are cover-incomparability graphs. In [6] it was proved that the recognition problem for cover-incomparability graphs is in general NP-complete. On the other hand there are classes of graphs (such as trees, Ptolemaic graphs, distance-hereditary graphs, block graphs, split graphs or k-trees) for which the recognition problem can be solved in linear time (see [2,3,7,8] for details and proofs).…”
Section: Introductionmentioning
confidence: 99%
“…
In this paper we continue investigations of cover-incomparability graphs of finite partially ordered sets (see [1,2,3,4] and [6,7]). We consider in some detail the distinction between cover-preserving subsets and isometric subsets of a partially ordered set.
…”
mentioning
confidence: 98%
“…covering, comparability and incomparability graph). In the paper that followed [8], it was shown that the complexity of recognizing whether a given graph is the C-I graph of some poset is in general NP-complete. In [1] the problem was investigated for the classes of split graphs and block graphs, and the C-I graphs within these two classes of graphs were characterized.…”
Section: Introductionmentioning
confidence: 99%